Automation of Dean's Office Functions in a Higher Education Institution on the Basis of Electronic Document Flow System. Issue 1 (2016) - Yarullin, Ilnar F.; Mumryayeva, Svetlana M.; Shalina, Olga N.; Safonov, Vladimir I.; Omarova, Vera K.
No abstract available